2006
DOI: 10.1080/09515070601058706
|View full text |Cite
|
Sign up to set email alerts
|

Counsellor facial expression and client-perceived rapport

Abstract: The effects of counsellors' facial expressions upon the degree of rapport experienced by a Standardized Client (STC) was assessed via examination of 59 counselling interviews conducted by graduate students in counselling. Izard's (1971) Affex system of classifying facial expressions was used to operationalize the independent variable of facial expression, with STC ratings of rapport on a five-point scale each minute of the interviews constituting the dependent variable. Data indicated that there was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 30 publications
0
26
0
1
Order By: Relevance
“…Training counseling students on the importance of nonverbal communication, such as smiling, can also be a very beneficial tool as they enter the practice of counseling. Sharpley et al (2006) suggested facial expressions that included smiling were significantly associated with the client's perception of high rapport with the counselor. Appropriate smiling (along with other nonverbals) by the counselor can be considered a critical skill that can aid in developing a positive counselor-client relationship.…”
Section: Implications For Counselingmentioning
confidence: 97%
See 1 more Smart Citation
“…Training counseling students on the importance of nonverbal communication, such as smiling, can also be a very beneficial tool as they enter the practice of counseling. Sharpley et al (2006) suggested facial expressions that included smiling were significantly associated with the client's perception of high rapport with the counselor. Appropriate smiling (along with other nonverbals) by the counselor can be considered a critical skill that can aid in developing a positive counselor-client relationship.…”
Section: Implications For Counselingmentioning
confidence: 97%
“…Moreover, research on genuine smiles reveals that smiling is associated with positive health and well-being (e.g., Harker & Keltner, 2001;Papa & Bonanno, 2008). Sharpley, Jeffrey, and McMah (2006) contended that a positive facial expression, including smiling, is a powerful behavior in developing a positive counselor-client relationship.…”
Section: Smiling As a Moderating Variable For Prejudicementioning
confidence: 99%
“…It is important to identify individuals prone to misinterpret neutral expressions as negative because they will likely feel uncomfortable in social interactions, including psychotherapeutic interactions, and, potentially, show behavioural responses to neutral expressions that may cause interactive and thus relationship problems that are common in traumatized individuals (Cloitre, Scarvalone, & Difede, 1997). There is evidence that specific facial expressions of therapists are associated with therapeutic relationship quality as perceived by the patient (Sharpley, Jeffrey, & Mcmah, 2006). If the negative interpretation bias we found extends to reallife situations, future research should explore if the therapeutic relationship with traumatized individuals can be improved by increasing therapists' awareness of their facial expressions and of their patients' responses to and interpretations of nonverbal signals of therapists and other interaction partners.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…According to Philippot et al ( 2003 ), it plays a role in the development of a good therapeutic alliance. The reliability of such intuitions represent a core aspect in recent years; accordingly several authors focused non-verbal interactions such as body movements (Ramseyer and Tschacher, 2011 , 2014 ), facial expressions (Sharpley et al, 2006 ), speech disruptions (Horiwitz et al, 1975 ), tone of voice (Wiseman and Rice, 1989 ), vocal quality (Tomicic et al, 2011 ), silences (Frankel and Levitt, 2008 ), and nonverbal prosodic aspects (Morán et al, 2016 ). On the whole, results highlighted that non-verbal interaction plays a core role in the development of the therapeutic relationship and its clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%